2021
DOI: 10.1016/j.heliyon.2021.e07897
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency vibration promotes AMPK-mediated glucose uptake in 3T3-L1 adipocytes

Abstract: Low-frequency vibration promotes AMPK-mediated glucose uptake in 3T3-L1 adipocytes, HELIYON, https://doi.org/10.1016/ j.heliyon.2021.e07897. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…LDH is used as an indicator of necrotic cell death (Cox et al, 2021; Haba et al, 2021). Cells were cultured for indicated times, and the culture media were collected for cytotoxicity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…LDH is used as an indicator of necrotic cell death (Cox et al, 2021; Haba et al, 2021). Cells were cultured for indicated times, and the culture media were collected for cytotoxicity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperglycemia originated from IR in patients with diabetes are predisposed to developing chronic wounds such as DFUs. Because IR could delay wound healing though interplay among impaired tissue regeneration, vasculopathy, neuropathy and in ammation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Drawing from these insights, we explored the effects of LLFV on improving glycometabolism and inflammation. Consequently, we previously demonstrated that LLFV of 50 Hz at 1000-1500 mVpp, which refers to the voltage applied to the vibrator, for 40 min/day for 5 days promoted AMP-activated protein kinase (AMPK)-mediated glucose transporter 4 (GLUT4) translocation and glucose uptake in 3T3-L1 adipocytes, 17 and LLFV of 600-1000 mVpp for 40 min/day promoted wound healing in the early phase of the healing process in a hyperglycemic rat model. 18 LLFV improved local glycometabolism, including promotion of GLUT4 expression and inhibition of methylglyoxal production-a major precursor of advanced glycation end-products.…”
mentioning
confidence: 99%
“…1,22 Additionally, the LLFV intensity for enhancing glucose uptake in adipocytes and promoting blood flow appeared to be different. 11,17 Therefore, we conceived to develop an intelligent vibration dressing to promote DFU wound healing via improvement of glucose uptake and blood flow at the wound site and autonomous optimization of vibration intensity based on the patient's insulin resistance and vasodilatory capacity using artificial intelligence (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation